English Dipthong Found in Song Titled Blue Jeans by Gangga Kusuma - Devi Wulandari; Dwi Indra Aprilliandari; Agci Hikmawati (Journal of Pedagogy and Education Science, 2022)
Diphthongs study the sound of language from process to change. This research covers "Blue Jeans" by famous singer-songwriter Gangga Kusuma, who started her career in 2018 with an emphasis on diphthong formation. Researchers choose English diphthongs for this research because it is important to listen to find the correct pronunciation in the learning process. Researchers use Roach's theory to divide diphthongs into two types. First, replace middle diphthongs such as /eɪ/, /aɪ/, /ɔɪ/, /әʊ/, /aʊ/ and second, /ɪə/, /eә/, /ʊә/. This study used a qualitative method and data were collected through a literature search. Analysis of the data revealed that Gangga Kusuma generated 26 examples of English diphthongs divided into 8 types. The diphthong /eɪ/ is used 9 times, the diphthong /aɪ/ is 8 times, the diphthong /ɔɪ/ is used only once, the diphthong /aʊ/ is used 2 times, and the diphthong /әʊ/ is used 5 times, diphthong ɪә/ is used only once, and some data samples are missing the diphthong /eә/ and /ʊә/. In other words, this study shows that Gangga Kusuma can make diphthong sounds that are consistent with those produced in normal diphthong production and the Oxford Advanced Learner's Dictionary. Furthurmore, it excels at producing a variety of diphthong sounds.